Prevalence of behavioral risk factors of non-communicable diseases in Mumbai: a descriptive cross-sectional study - Paslawar, Srilatha K.; Kalaskar, Shrikant K. (International Journal Of Community Medicine And Public Health, 2024)
Background: Globalization and urbanization have led to lifestyle changes among urban poor, which need to be understood, as the urban areas are undergoing rapid transitions. The behavioral risk factors are mainly responsible for the causation of non-communicable diseases (NCD). Objectives were to know prevalence and pattern of behavioral risk factors for NCDs in Naigoan, BDD Chawl, Mumbai to initiate steps for preventive interventions. Methods: This was community based cross-sectional study conducted among residents of Naigaon, BDD Chawl, Mumbai, India. Data were collected by the house-to-house survey using predesigned and pretested Performa. The world health organization-stepwise approach was used for chronic disease risk factor surveillance. Descriptive statistics and chi-square test were used for analysis. Results: About 65% of the respondents use smokeless form of tobacco, while 19% are using smoke form of tobacco. Among tobacco users nearly half have been using tobacco for the past 16 years. Nearly half (48%) of respondents were current alcohol drinkers. All the respondents in the study population consume less than five servings of fruits and vegetables which is less than WHO recommended servings. About 67% of the respondents were involved in the moderate type of activities. Conclusions: Study found high prevalence of NCD risk factors in the population. These risk factors have been prevalent since more than decade so, there may be very high burden of NCD soon in the study area. Screening and IEC activities need to be strengthened for diagnosis and preventive measures can be implemented at early stage of life.